Analisis Beban Kerja pada Proses Pengangkatan Pupuk ke Dalam Truck Menggunakan Metode Standard Nordic Quistionaire dan Niosh Lifting Equation di PT. Pupuk Iskandar Muda - Sofiyanurriyanti, Sofiyanurriyanti; Rezayansyah, Okta; Ardiyansyah, Agus (Universitas Teuku Umar, 2020)
This research was conducted at PT. Pupuk Iskandar Muda in the warehouse section I, which aims to analyze and identify the level of musculoskletal disorders experienced by operators when lifting fertilizers into trucks using Standard Nordic Quistionaire (SNQ). Determining workload using the NIOSH Lifting Equation method with the Biomechanics Software Tool where the tool aims to analyze quickly and easily in terms of postural activities experienced by a person's body and also provide a value of several levels of risk at work. The category of action with the assessment of biomechanical software is that the RWL value is obtained Recommended Weight Limit (RWL) = 13.174 and Lifting Index = 3,7951 Because LI > 1, this activity contains a risk of spinal injury for workers and the work method should not be maintained . Because this work can be categorized as dangerous for workers, the researchers recommend a tool to facilitate loading and compiling fertilizer into the truck in the form of a trolly that can move flexibly back and forth and can be placed in a truck carrying out loading and unloading.Â